Legal framework to regulate nutraceuticals in Malaysia - Sahida Safuan (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2020)
The growing consciousness among consumers on the importance of health has resulted in the mushrooming of various nutraceuticals products in the market. Nutraceutical products have become widespread phenomenon for proclaimed benefits they seem to offer. To define what nutraceutical is, has always been confusing in certain jurisdictions especially Malaysia. Legally, they cannot be considered as mere food, and they are not pharmaceutical drugs either. The issue arises is in relation to the absence of proper regulation that controls the production of nutraceuticals products. One of the main problems is the fact that nutraceuticals products in itself is not a standalone category. In Malaysia, nutraceuticals can be classified either as food or drugs and be regulated by different regulatory agencies depending on its classification. This creates a double standard treatment as different agencies have different standard procedures to govern the product. Due to uncertainty in its categorisation, nutraceutical manufacturers have taken advantage in producing and marketing those products to consumers. Social media has been effectively used as a platform to market these products. It is observed that some online seller in attracting customers' attention has advertised numerous claims. To some extent, there are sellers that claim that their product able to cure diseases that science had yet to find cure for such as cancer and diabetics. The popular marketing strategy by displaying the testimony of the users allows the producers to make profit out of the unproven claims of their products. As Malaysia is aimed to be the world class-leading supplier for nutraceutical products under the Economic Transformation Programme's Agriculture National Key Economic Area, there is a need to upgrade the local herbal supplements in the sense that any health claims must be supported by clinical evidence. Thus, a proper regulation in restraining such producers from advertising unsupported health claim is highly needed and required in protecting the consumers' interests.This study aims to examine regulatory issues pertaining to the production and marketing processes of nutraceuticals to ensure safer consumption. This study propose that there is a real need to have a specific, standard procedure to safeguard and protect consumer's interest in the long run. The study adopts a qualitative approach that includes doctrinal analysis and semi-structured interviews with relevant authorities. It is proposed that for local atmosphere, governmental intervention is required to assure safer consumption of nutraceutical products so that consumers may truly benefit from them. Self-regulation as practiced at present has to some extent, placed the nutraceutical industry in a very complacent position, resulting in consumers' safety at stake.